Inequality, macroeconomic performance and political polarization: An empirical analysis - Christian Proa\~no Acosta; Juan Carlos Pe\~na; Thomas Saalfeld (Bamberg University, Bamberg Economic Research Group (BERG), 2019)
This paper investigates the macroeconomic and social determinants of voting behavior, and especially of political polarization, for 20 advanced countries using annual data ranging from 1970 to 2016 and covering 291 parliamentary elections. Using a panel estimation approach and rolling regressions we find empirical evidence supporting that a) traditionally established mainstream parties (center-left, center, and center-right) are penalized for poor economic performance; b) far-left (populist and radical parties) parties benefit from increasing unemployment rates; c) greater income inequality has increased the electoral support for far-right parties, particularly in recent times. Further, we do not find empirical support for the notion that social and economic globalization has led to an increase of popularity of far-right parties. These results have wide reaching implications for the current political situation in the Western world.
Keywords: E12; E24; E32; E44; 330; Income Inequality; Political Polarization; Globalization; Economic Voting Behavior